Domain walls and anchoring transitions mimicking nematic biaxiality in the oxadiazole bent-core liquid crystal C7. Issue 20 (30th March 2015) - Kim, Young-Ki; Cukrov, Greta; Xiang, Jie; Shin, Sung-Tae; Lavrentovich, Oleg D.
Abstract : "Secondary disclinations" previously considered as evidence of a biaxial nematic phase are shown to be domain walls in a uniaxial nematic phase. Abstract : We investigate the origin of "secondary disclinations" that were recently described as new evidence of a biaxial nematic phase in an oxadiazole bent-core thermotropic liquid crystal C7. Using an assortment of optical techniques such as polarizing optical microscopy, LC PolScope, and fluorescence confocal polarizing microscopy, we demonstrate that the secondary disclinations represent non-singular domain walls formed in a uniaxial nematic phase during the surface anchoring transition, in which surface orientation of the director changes from tangential (parallel to the bounding plates) to tilted. Each domain wall separates two regions with the director tilted in opposite azimuthal directions. At the centre of the wall, the director remains parallel to the bounding plates. The domain walls can be easily removed by applying a moderate electric field. The anchoring transition is explained by the balance of (a) the intrinsic perpendicular surface anchoring produced by the polyimide aligning layer and (b) tangential alignment caused by ionic impurities forming electric double layers. The model is supported by the fact that the temperature of the tangentially tilted anchoring transition decreases as the cell thickness increases and as the concentration of ionic species (added salt) increases. We also demonstrate that the surface alignment is strongly affected by thermal degradation of the samples. This study shows that C7 exhibits only a uniaxial nematic phase and demonstrates yet another mechanism (formation of "secondary disclinations") by which a uniaxial nematic phase can mimic a biaxial nematic behaviour.